Penguatan Kompetensi Guru Sekolah Minggu HKBP Jambi melalui Pendampingan - Pison Sinambela (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
This service aims to improve the capacity of Sunday school teachers at HKBP Jambi so they can perform their teaching and coaching roles effectively, consistently, and in context. Children’s faith education through Sunday school is important for shaping character, spiritual growth, and understanding of the faith among the younger generation. However, many Sunday school teachers face challenges related to their pedagogical competence, spirituality, and relationships. The methods used include direct mentoring for 30 Sunday School teachers through identification of need, group discussion, creative method training, and also application of Robert Raikes service principle, such as: commitment, loyalty, and reliability based on Matthew 20:28. The service result show an improvement in the teachers’ abilities to deliver Bible material interactively, guiding children personally, building stable relationship, and also applying Raikes’ principles in teaching. Teachers are beginning to understand Sunday school ministry as a spiritual calling that demands full dedication, not just a routine task, and are also able to use creative methods such as storytelling, spiritual games, and small-group discussions